Tryptase and IgE concentrations in the respiratory tract of infants with acute bronchiolitis. Issue 1 (January 1995) - Everard, M L; Fox, G; Walls, A F; Quint, D; Fifield, R; Walters, C; Swarbrick, A; Milner, A D
Abstract : It has been proposed that a specific IgE response contributes to the immunopathology of acute respiratory syncytial virus (RSV) bronchiolitis but previous work has been difficult to replicate. Indirect evidence that might support this contention was sought by measuring total IgE concentrations in bronchoalveolar lavage (BAL) samples obtained from intubated infants and by attempting to detect mRNA for IgE in cells obtained from both the upper and lower respiratory tract. Evidence of significant mast cell activation was sought by measuring tryptase concentrations in BAL fluid and serum. Detectable concentrations of IgE were found in two of seven BAL samples obtained more than five days after intubation and mRNA for IgE was demonstrated in three of six BAL samples and three of six samples obtained from the upper respiratory tract. Tryptase was detectable in 11 of 12 BAL samples with the two highest values detected on day 1. These values were raised compared with control samples but were not such to suggest that mast cell degranulation is the major contributor to the inflammatory process. These results suggest that IgE may be produced in the airways of infants in response to RSV infection. The relationships between IgE production, RSV infection, and symptoms of acute bronchiolitis remain obscure.